Relationship between perceived supervisory style and satisfaction among undergraduate couselling interns of public universities in Malaysia - Mohd Ali, Nur Hafizah (2013)
Counselling supervision is an essential element to novice counsellors in developing their professional and competency during internship. Supervisors play different roles and styles during supervision process. The supervisory styles of supervisors in Malaysia and its relationship to the supervisory satisfaction has not been explored and investigated thoroughly. Therefore,this study aims (a) to identify the prevalent supervisory styles among supervisors as perceived by counselling interns in Malaysian public universities; (b) to examine the significant relationship between perceived supervisory styles and supervisory satisfaction among counselling interns in Malaysian public universities; and (c) to examine whether the perceived supervisory styles significantly explained supervisory satisfaction among counselling interns during supervision process. A stratified random sampling technique was performed to select 138 respondents among counselling interns from four public universities in Malaysia. A descriptive and correlational research design was used in this study. Two types of inventories were used. The Adapted Supervisory Styles Inventory was used to measure four supervisory styles (Directive Teacher style, Supportive Teacher style, Counsellor style and Consultant style) as perceived by counselling interns and the Supervisory Satisfaction Questionnaire was used to measure satisfaction of counselling intern towards supervision. The findings revealed that the majority of respondents perceived their supervisors adapted supportive teacher style (44.9%) followed by directive teacher style (40.6%) during supervision. The findings also revealed that only three types of supervisory styles have significant relationship with supervisory satisfaction. The three styles are Directive Teacher style (r= .42,p< .05), Supportive Teacher style (r= .47, p< .05) and Counsellor style (r=.32, p< .05). While the Consultant style is the only style that has no significant relationship with supervisory satisfaction (r= .10, p> .05). The result also showed that from four types of supervisory styles perceived by counselling interns, only Supportive Teacher style was significantly contribute to supervisory satisfaction (R2= .24, F(3, 134)= 13.93, p< .001). The Supportive Teacher style was significantly explained 23.8% of the supervisory satisfaction among the counselling interns. This study, thus, has filled the knowledge gap in counselling supervisory styles. The newly adapted instruments of supervisory styles inventory can be extended to the undergraduate level interns. Practically, it helps to enlighten supervisors in enhancing supervision process. Supervisors or counselor educators have to find the most functional and appropriate style that suit their interns.